Glutathione biosynthesis is upregulated at the initiation of MYCN‐driven neuroblastoma tumorigenesis. Issue 6 (2nd March 2016) - Carter, Daniel R.; Sutton, Selina K.; Pajic, Marina; Murray, Jayne; Sekyere, Eric O.; Fletcher, Jamie; Beckers, Anneleen; De Preter, Katleen; Speleman, Frank; George, Rani E.; Haber, Michelle; Norris, Murray D.; et al.
Abstract : The MYCN gene is amplified and overexpressed in a large proportion of high stage neuroblastoma patients and has been identified as a key driver of tumorigenesis. However, the mechanism by which MYCN promotes tumor initiation is poorly understood. Here we conducted metabolic profiling of pre‐malignant sympathetic ganglia and tumors derived from the TH‐MYCN mouse model of neuroblastoma, compared to non‐malignant ganglia from wildtype littermates. We found that metabolites involved in the biosynthesis of glutathione, the most abundant cellular antioxidant, were the most significantly upregulated metabolic pathway at tumor initiation, and progressively increased to meet the demands of tumorigenesis. A corresponding increase in the expression of genes involved in ribosomal biogenesis suggested that MYCN‐driven transactivation of the protein biosynthetic machinery generated the necessary substrates to drive glutathione biosynthesis. Pre‐malignant sympathetic ganglia from TH‐MYCN mice had higher antioxidant capacity and required glutathione upregulation for cell survival, when compared to wildtype ganglia. Moreover, in vivo administration of inhibitors of glutathione biosynthesis significantly delayed tumorigenesis when administered prophylactically and potentiated the anticancer activity of cytotoxic chemotherapy against established tumors. Together these results identify enhanced glutathione biosynthesis as a selective metabolic adaptation required for initiation of MYCN‐driven neuroblastoma, and suggest that glutathione‐targeted agents may be used as a potential preventative strategy, or as an adjuvant to existing chemotherapies in established disease. Highlights: Metabolomics in TH‐MYCN mice demonstrates early upregulation of glutathione biosynthesis. MYCN increases protein biosynthesis to satisfy the substrate demand for glutathione production. Glutathione acts as an antioxidant mechanism for pre‐cancer cell survival at tumor initiation.